The Development of Maharah Kitabah in the Millenial Era: An Analysis of Natiq Book - Hakim Syukri Alhamda (Arabic Education Program IAIN Pekalongan, 2022)
This study aims to reveal the methods used in Natiq book in developing sentences, bound expressions, free expressions, and constructing paragraphs in Arabic papers. Natiq book is an alternative learning source for learning maharah kitabah (writing skills) in the millennial era. This research used descriptive analysis methods with the type of library research that utilizes library sources to obtain research data. This study reveals that emerge from this research are developments in learning maharah kitabah, especially first, in writing Arabic expressions; second, constructing sentences; third, bound expressions, free expressions, and fourth, constructing paragraphs in Arabic papers. The conclusion is that the Natiq book volume 3, which is recommended by the Qatar mutanadzir (debater) and Saudi Arabian Sheikh and the Indonesian mawapres (Indonesian most outstanding student), can be used as an alternative learning materials/source for developing maharah kitabah in Arabic language learning today, especially for Islamic college students in the Arabic Language Education study program. From the results of the analysis of this textbook, it is clear that the Natiq method book volume 3 can bring a solution to the problems of developing maharah kitabah in Arabic language learning today, especially for Islamic college students.